Principles of dressing and debridement in modern rural surgery: experience of a case of Fournier’s gangrene - Baruah, Arijit Rumu; Kalita, Darpana (International Surgery Journal, 2024)
Fournier’s gangrene is a rare and rapidly progressive necrotising fasciitis of the external genitalia and perineum. It is characterised by obliterative endarteritis of the subcutaneous arteries resulting in gangrene of the subcutaneous tissue and the overlying skin. Rural surgery refers to the practice of surgery serving people in rural communities and geographically remote areas. Rural surgery faces multiple challenges like limitation of resources and manpower, poverty, multiple co-morbidities and superstitions. We present such a case of Fournier’s gangrene treated in a secondary care centre of rural Assam. A 45 year old male presented with pain and discharge from the scrotum since two weeks. No other co-morbidities were present. Initially, wound debridement and dressing with hydrogen peroxide and povidone iodine is done. Necrosed tissue is sent for microbial culture and sensitivity. Initially, empirical antibiotics was started and was converted to fluoroquinolones as it showed sensitivity. Serial dressing and debridement were continued till healthy granulation tissue appeared. Then, the wound was closed by loose approximation method. Wound was successfully apposed and viability of both the testis was also found to be intact. Thus, the age-old principle of dressing and debridement still serves as the background of wound care in modern rural surgery.